Development and Characterization of PLA/PCL Blend Filaments and 3D Printed Scaffolds - Eryildiz, Meltem; Karakus, Aleyna; Eksi, Mihrigul Altan (SPRINGER, 2025)
This study investigates the manufacturing and characterization of polylactic acid (PLA)/polycaprolactone (PCL) blend filaments and 3D printed scaffolds for tissue engineering applications. This research provides a comprehensive investigation into both the PLA/PCL filament fabrication process and the subsequent 3D printing of PLA/PCL scaffolds. PLA/PCL blends have been prepared with a twin-screw extruder, followed by filament fabrication and 3D printing. The resulting samples underwent thorough characterization through mechanical, thermal, chemical, morphological, and rheological analyses, all tailored toward their application in tissue engineering. Results revealed that the addition of 20 wt. % PCL resulted in PLA/PCL blend scaffolds with improved mechanical and thermal properties, showing promise for future tissue engineering applications. This study provides novel insights into the fabrication and properties of PLA/PCL scaffolds, advancing the understanding of their potential in tissue engineering and offering valuable guidance for future research efforts in this domain.
Keywords: 3D printing; filament preparation; mechanical properties; PLA/PCL blends; scaffold fabrication; Materials Science